Insertion sequence polymorphism and genomic rearrangements uncover hidden Wolbachia diversity in Drosophila suzukii and D. subpulchrella - Rupinder Kaur (Nature Portfolio, 2017)
Abstract Ability to distinguish between closely related Wolbachia strains is crucial for understanding the evolution of Wolbachia-host interactions and the diversity of Wolbachia-induced phenotypes. A useful model to tackle these issues is the Drosophila suzukii – Wolbachia association. D. suzukii, a destructive insect pest, harbor a non-CI inducing Wolbachia ‘wSuz’ closely related to the strong CI-inducing wRi strain. Multi locus sequence typing (MLST) suggests presence of genetic homogeneity across wSuz strains infecting European and American D. suzukii populations, although different Wolbachia infection frequencies and host fecundity levels have been observed in both populations. Currently, it is not clear if these differences are due to cryptic wSuz polymorphism, host background, geographical factors or a combination of all of them. Here, we have identified geographical diversity in wSuz in D. suzukii populations from different continents using a highly diagnostic set of markers based on insertion sequence (IS) site polymorphism and genomic rearrangements (GR). We further identified inter-strain diversity between Wolbachia infecting D. suzukii and its sister species D. subpulchrella (wSpc). Based on our results, we speculate that discernible wSuz variants may associate with different observed host phenotypes, a hypothesis that demands future investigation. More generally, our results demonstrate the utility of IS and GRs in discriminating closely related Wolbachia strains.